HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN LURUS ATLET PPLP PENCAK SILAT DISPORA RIAU - Harromaini, Harromaini; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the observation that has been done against athletes PPLP Pencak Silat Dispora Riau discovered several phenomena such as: it appears that the ability of straight kick committed athlete is still less than the maximum, this is caused by not maximal physical elements athletes such as leg muscle strength athletes who are not maximized, so straight kick that do not powered. Less good balance of athletes will also affect the speed of straight kick committed athlete. Coordination of movement that the athlete is also not maximized, it will affect the results straight kick, the kick will be easily anticipated by the opponent to do the rebuttal, dodgery, and even easier for your opponent to counterattack quickly and suddenly. Straight kick in the sport of martial arts have to do with the strong leg muscle power with the ability range at the target so that the opponent difficult to parry and dodgery. The purpose of this study was to determine the relationship of limb muscle power with the ability to kick straight PPLP Pencak Silat athletes Riau. This research is done using this type of research correlational. Correlational is a statistical tool,which can be used to compre the result of measurement of two different variables in order to determine the degree of correlation between the variables. Populasi and csample in this research as all PPLP Pencak silat athletes Riau active Dispora martial arts training totaling 12 people. The data collection technique is to use technique total sampling. Based on the research that has been done can be concluded that there is a relationship to the ability of leg muscle power speed sport straight kick in pencak silat athletes PPLP Dispora Riau count r=0.796 and significant level = 0.5 was faound r =0.602 with the category table there is a significant relationship.Keywords: leg muscle power, speed capability straight kick